sin ( A ) sin ( 6 0 − A ) sin ( 6 0 + A ) = x 1 sin 3 A F i n d : ( 1 . 5 ) ( x ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
yeah man that's correct :)
sin ( 6 0 − A ) = 2 3 cos A − 2 1 sin A sin ( 6 0 + A ) = 2 3 cos A + 2 1 sin A t h e n , sin A . sin ( 6 0 − A ) . sin ( 6 0 + A ) = sin A . [ 2 3 cos A − 2 1 sin A ] . [ 2 3 cos A + 2 1 sin A ] = sin A . [ 4 3 cos 2 A − 4 1 sin 2 A ] b u t , cos 2 A = 2 1 [ 1 + cos A ] sin 2 A = 2 1 [ 1 − cos A ] t h e n , = sin A . 8 3 ( 1 + cos 2 A ) − 8 1 ( 1 − cos 2 A ) = sin A . [ 8 3 + 8 3 cos 2 A − 8 1 + 8 1 cos 2 A ] = 8 2 sin A + 8 4 sin A . cos 2 A b u t , sin A . cos 2 A = 2 1 [ sin 3 A − sin A ] t h e n , = 8 2 sin A + 8 2 sin 3 A − 8 2 sin A = 4 1 sin A S o , t h e a n s w e r i s x = 4 1 . 5 x = 6
Since 4sin(60-A)sinAsin(60+A)=sin3A So 1.5*4=6.
How do you know that?
Log in to reply
L H S = sin A sin ( 6 0 − A ) sin ( 6 0 + A ) = sin ( A ) [ s i n 2 6 0 − s i n 2 A ] = sin ( A ) [ 4 3 − s i n 2 A ] = 4 3 sin ( A ) − s i n 3 A = 4 1 [ 3 sin ( A ) − 4 s i n 3 A ] = 4 1 sin ( 3 A ) = R H S
i hope this helps :)
Remember to give justification of whatever you write in your solution
Problem Loading...
Note Loading...
Set Loading...
Equipped with the knowledge that this is an identity (since there is only one possible answer for x ) we simply plug in a value for A and solve for x .
We plug in x = 3 0 ∘ to get sin 3 0 sin 3 0 sin 9 0 = x 1 sin 9 0
Solving gives x 1 = 4 1 ⟹ x = 4
Thus the answer is 1 . 5 × 4 = 6